3T vs. 7T fMRI: capturing early human memory consolidation after motor task utilizing the observed higher functional specificity of 7T - Kreitz, Silke; Mennecke, Angelika; Konerth, Laura; Rösch, Julie; Nagel, Armin Michael; Laun, Frederik Bernd; Uder, Michael; Dörfler, Arnd; Heß, Andreas (Frontiers in Neuroscience, 2023)
Objective: Functional magnetic resonance imaging (fMRI) visualizes brain structures at increasingly higher resolution and better signal-to-noise ratio (SNR) as field strength increases. Yet, mapping the blood oxygen level dependent (BOLD) response to distinct neuronal processes continues to be challenging. Here, we investigated the characteristics of 7 T-fMRI compared to 3 T-fMRI in the human brain beyond the effect of increased SNR and verified the benefits of 7 T-fMRI in the detection of tiny, highly specific modulations of functional connectivity in the resting state following a motor task. Methods: 18 healthy volunteers underwent two resting state and a stimulus driven measurement using a finger tapping motor task at 3 and 7 T, respectively. The SNR for each field strength was adjusted by targeted voxel size variation to minimize the effect of SNR on the field strength specific outcome. Spatial and temporal characteristics of resting state ICA, network graphs, and motor task related activated areas were compared. Finally, a graph theoretical approach was used to detect resting state modulation subsequent to a simple motor task. Results: Spatial extensions of resting state ICA and motor task related activated areas were consistent between field strengths, but temporal characteristics varied, indicating that 7 T achieved a higher functional specificity of the BOLD response than 3 T-fMRI. Following the motor task, only 7 T-fMRI enabled the detection of highly specific connectivity modulations representing an “offline replay” of previous motor activation. Modulated connections of the motor cortex were directly linked to brain regions associated with memory consolidation. Conclusion: These findings reveal how memory processing is initiated even after simple motor tasks, and that it begins earlier than previously shown. Thus, the superior capability of 7 T-fMRI to detect subtle functional dynamics promises to improve diagnostics and therapeutic assessment of neurological diseases.
CRIS-Team Scopus Importer:2023-09-08
Keywords: 7T fMRI; graph theory; memory; motor task; offline replay; resting state

3T vs. 7T fMRI: capturing early human memory consolidation after motor task utilizing the observed higher functional specificity of 7T - Kreitz, Silke; Mennecke, Angelika; Konerth, Laura; Rösch, Julie; Nagel, Armin Michael; Laun, Frederik Bernd; Uder, Michael; Dörfler, Arnd; Heß, Andreas (Frontiers in Neuroscience, 2023)
Functional magnetic resonance imaging (fMRI) visualizes brain structures at increasingly higher resolution and better signal-to-noise ratio (SNR) as field strength increases. Yet, mapping the blood oxygen level dependent (BOLD) response to distinct neuronal processes continues to be challenging. Here, we investigated the characteristics of 7 T-fMRI compared to 3 T-fMRI in the human brain beyond the effect of increased SNR and verified the benefits of 7 T-fMRI in the detection of tiny, highly specific modulations of functional connectivity in the resting state following a motor task.<br

7T MRI features in control human hippocampus and hippocampal sclerosis: An ex vivo study with histologic correlations - Coras, Roland; Milesi, Gloria; Zucca, Ileana; Mastropietro, Alfonso; Scotti, Alessandro; Figini, Matteo; Muehlebner, Angelika; Heß, Andreas; Graf, Wolfgang; Tringali, Giovanni; Blümcke, Ingmar; Villani, Flavio; et al. (Epilepsia, 2014)
Hippocampal sclerosis (HS) is the major structural brain lesion in patients with temporal lobe epilepsy (TLE). However, its internal anatomic structure remains difficult to recognize at 1.5 or 3 Tesla (T) magnetic resonance imaging (MRI), which allows neither identification of specific pathology patterns nor their proposed value to predict postsurgical outcome, cognitive impairment, or underlying etiologies. We aimed to identify specific HS subtypes in resected surgical TLE samples on 7T MRI by juxtaposition with corresponding histologic sections.Fifteen nonsclerotic and 18 sclerotic hippocampi were studied ex vivo using an experimental 7T MRI scanner. T2 -weighted images (T2wi) and diffusion tensor imaging (DTI) data were acquired and validated using a systematic histologic analysis of same specimens along the anterior-posterior axis of the hippocampus.In nonsclerotic hippocampi, differences in MR intensity could be assigned to seven clearly recognizable layers and anatomic boundaries as confirmed by histology. All hippocampal subfields could be visualized also in the hippocampal head with three-dimensional imaging and angulated coronal planes. Only four discernible layers were identified in specimens with histopathologically confirmed HS. All sclerotic hippocampi showed a significant atrophy and increased signal intensity along the pyramidal cell layer. Changes in DTI parameters such as an increased mean diffusivity, allowed to distinguish International League Against Epilepsy (ILAE) HS type 1 from type 2. Whereas the increase in T2wi signal intensities could not be attributed to a distinct specific histopathologic substrate, that is, decreased neuronal or increased glial cell densities, intrahippocampal projections and fiber tracts were distorted in HS specimens suggesting a complex disorganization of the cellular composition, fiber networks, as well as its extracellular matrix.Our data further advocate high-resolution MRI as a helpful and promising diagnostic tool for the investigation of hippocampal pathology along the anterior-posterior extent in TLE, as well as in other neurologic and neurodegenerative disorder
EVALuna2:7255

Acceleration of vascularized bone tissue-engineered constructs in a large animal model combining intrinsic and extrinsic vascularization - Weigand, Annika; Beier, Justus; Heß, Andreas; Gerber, Thomas; Arkudas, Andreas; Horch, Raymund E.; Boos, Anja (Tissue Engineering: Parts A, B, and C, 2015)
During the last decades, a range of excellent and promising strategies in Bone Tissue Engineering have been developed. However, the remaining major problem is the lack of vascularization. In this study, extrinsic and intrinsic vascularization strategies were combined for acceleration of vascularization. For optimal biomechanical stability of the defect site and simplifying future transition into clinical application, a primary stable and approved nanostructured bone substitute in clinically relevant size was used. An arteriovenous (AV) loop was microsurgically created in sheep and implanted, together with the bone substitute, in either perforated titanium chambers (intrinsic/extrinsic) for different time intervals of up to 18 weeks or isolated Teflon(®) chambers (intrinsic) for 18 weeks. Over time, magnetic resonance imaging and micro-computed tomography (CT) analyses illustrate the dense vascularization arising from the AV loop. The bone substitute was completely interspersed with newly formed tissue after 12 weeks of intrinsic/extrinsic vascularization and after 18 weeks of intrinsic/extrinsic and intrinsic vascularization. Successful matrix change from an inorganic to an organic scaffold could be demonstrated in vascularized areas with scanning electron microscopy and energy dispersive X-ray spectroscopy. Using the intrinsic vascularization method only, the degradation of the scaffold and osteoclastic activity was significantly lower after 18 weeks, compared with 12 and 18 weeks in the combined intrinsic-extrinsic model. Immunohistochemical staining revealed an increase in bone tissue formation over time, without a difference between intrinsic/extrinsic and intrinsic vascularization after 18 weeks. This study presents the combination of extrinsic and intrinsic vascularization strategies for the generation of an axially vascularized bone substitute in clinically relevant size using a large animal model. The additional extrinsic vascularization promotes tissue ingrowth and remodeling processes of the bone substitute. Extrinsic vessels contribute to faster vascularization and finally anastomose with intrinsic vasculature, allowing microvascular transplantation of the bone substitute after a shorter prevascularization time than using the intrinsic method only. It can be reasonably assumed that the usage of perforated chambers can significantly reduce the time until transplantation of bone constructs. Finally, this study paves the way for further preclinical testing for proof of the concept as a basis for early clinical applicability.
EVALuna2:15582

A consensus protocol for functional connectivity analysis in the rat brain - Grandjean, Joanes; Desrosiers-Gregoire, Gabriel; Anckaerts, Cynthia; Angeles-Valdez, Diego; Ayad, Fadi; Barrière, David A.; Blockx, Ines; Bortel, Aleksandra; Broadwater, Margaret; Cardoso, Beatriz M.; Célestine, Marina; Chavez-Negrete, Jorge E.; et al. (Nature Neuroscience, 2023)
Task-free functional connectivity in animal models provides an experimental framework to examine connectivity phenomena under controlled conditions and allows for comparisons with data modalities collected under invasive or terminal procedures. Currently, animal acquisitions are performed with varying protocols and analyses that hamper result comparison and integration. Here we introduce StandardRat, a consensus rat functional magnetic resonance imaging acquisition protocol tested across 20 centers. To develop this protocol with optimized acquisition and processing parameters, we initially aggregated 65 functional imaging datasets acquired from rats across 46 centers. We developed a reproducible pipeline for analyzing rat data acquired with diverse protocols and determined experimental and processing parameters associated with the robust detection of functional connectivity across centers. We show that the standardized protocol enhances biologically plausible functional connectivity patterns relative to previous acquisitions. The protocol and processing pipeline described here is openly shared with the neuroimaging community to promote interoperability and cooperation toward tackling the most important challenges in neuroscience.
CRIS-Team Scopus Importer:2023-04-07

Activity and connectivity changes of central projection areas revealed by functional magnetic resonance imaging in NaV1.8-deficient mice upon cold signaling - Heindl-Erdmann, Cornelia; Zimmermann, Katharina; Reeh, Peter; Brune, Kay; Heß, Andreas (Scientific Reports, 2017)
The voltage-gated sodium channel subtype NaV1.8 is expressed in the peripheral nervous system in primary afferent nociceptive C-fibers and is essential for noxious cold signaling. We utilized functional magnetic resonance imaging on NaV1.8-deficient (NaV1.8(-/-)) compared with wildtype (WT) mice to identify brain structures decoding noxious cold and/or heat signals. In NaV1.8(-/-) mice functional activity patterns, activated volumes and BOLD signal amplitudes are significantly reduced upon noxious cold stimulation whereas differences of noxious heat processing are less pronounced. Graph-theoretical analysis of the functional connectivity also shows dramatic alterations in noxious cold sensation in NaV1.8(-/-) mice and clearly reduced interactions between certain brain structures. In contrast, upon heat stimulation qualitatively quite the same functional connectivity pattern and consequently less prominent connectivity differences were observed between NaV1.8(-/-) and WT mice. Thus, the fact that NaV1.8(-/-) mice do not perceive nociceptive aspects of strong cooling in contrast to their WT littermates seems not only to be a pure peripheral phenomenon with diminished peripheral transmission, but also consists of upstream effects leading to altered subsequent nociceptive processing in the central nervous system and consequently altered connectivity between pain-relevant brain structures.
EVALuna2:2489

Adult alcohol drinking and emotional tone are mediated by neutral sphingomyelinase during development in males - Kalinichenko, Liubov; Mühle, Christiane; Jia, Tianye; Anderheiden, Felix; Datz, Maria; Eberle, Anna-Lisa; Eulenburg, Volker; Granzow, Jonas; Hofer, Martin Jürgen; Hohenschild, Julia; Huber, Sabine; Kämpf, Stefanie; et al. (Cerebral Cortex, 2022)
Alcohol use, abuse, and addiction, and resulting health hazards are highly sex-dependent with unknown mechanisms. Previously, strong links between the SMPD3 gene and its coded protein neutral sphingomyelinase 2 (NSM) and alcohol abuse, emotional behavior, and bone defects were discovered and multiple mechanisms were identified for females. Here we report strong sex-dimorphisms for central, but not for peripheral mechanisms of NSM action in mouse models. Reduced NSM activity resulted in enhanced alcohol consumption in males, but delayed conditioned rewarding effects. It enhanced the acute dopamine response to alcohol, but decreased monoaminergic systems adaptations to chronic alcohol. Reduced NSM activity increased depression- and anxiety-like behavior, but was not involved in alcohol use for the self-management of the emotional state. Constitutively reduced NSM activity impaired structural development in the brain and enhanced lipidomic sensitivity to chronic alcohol. While the central effects were mostly opposite to NSM function in females, similar roles in bone-mediated osteocalcin release and its effects on alcohol drinking and emotional behavior were observed. These findings support the view that the NSM and multiple downstream mechanism may be a source of the sex-differences in alcohol use and emotional behavior.
CRIS-Team WoS Importer:2022-04-15
Keywords: neutral sphingomyelinase; osteocalcin; depression; alcohol; anxiety

A New Analysis of Resting State Connectivity and Graph Theory Reveals Distinctive Short-Term Modulations due to Whisker Stimulation in Rats - Kreitz, Silke; De Celis Alonso, Benito; Uder, Michael; Heß, Andreas (Frontiers in Neuroscience, 2018)
Resting state (RS) connectivity has been increasingly studied in healthy and diseased brains in humans and animals. This paper presents a new method to analyze RS data from fMRI that combines multiple seed correlation analysis with graph-theory (MSRA). We characterize and evaluate this new method in relation to two other graph-theoretical methods and ICA. The graph-theoretical methods calculate cross-correlations of regional average time-courses, one using seed regions of the same size (SRCC) and the other using whole brain structure regions (RCCA). We evaluated the reproducibility, power, and capacity of these methods to characterize short-term RS modulation to unilateral physiological whisker stimulation in rats. Graph-theoretical networks found with the MSRA approach were highly reproducible, and their communities showed large overlaps with ICA components. Additionally, MSRA was the only one of all tested methods that had the power to detect significant RS modulations induced by whisker stimulation that are controlled by family-wise error rate (FWE). Compared to the reduced resting state network connectivity during task performance, these modulations implied decreased connectivity strength in the bilateral sensorimotor and entorhinal cortex. Additionally, the contralateral ventromedial thalamus (part of the barrel field related lemniscal pathway) and the hypothalamus showed reduced connectivity. Enhanced connectivity was observed in the amygdala, especially the contralateral basolateral amygdala (involved in emotional learning processes). In conclusion, MSRA is a powerful analytical approach that can reliably detect tiny modulations of RS connectivity. It shows a great promise as a method for studying RS dynamics in healthy and pathological conditions.
EVALuna2:34696

Animal Functional Magnetic Resonance Imaging: Trends and Path Toward Standardization - Mandino, Francesca; Cerri, Domenic H.; Garin, Clement M.; Straathof, Milou; van Tilborg, Geralda A.F.; Chakravarty, M. Mallar; Dhenain, Marc; Dijkhuizen, Rick M.; Gozzi, Alessandro; Heß, Andreas; Keilholz, Shella D.; Lerch, Jason P.; et al. (Frontiers in Neuroinformatics, 2020)
Animal whole-brain functional magnetic resonance imaging (fMRI) provides a non-invasive window into brain activity. A collection of associated methods aims to replicate observations made in humans and to identify the mechanisms underlying the distributed neuronal activity in the healthy and disordered brain. Animal fMRI studies have developed rapidly over the past years, fueled by the development of resting-state fMRI connectivity and genetically encoded neuromodulatory tools. Yet, comparisons between sites remain hampered by lack of standardization. Recently, we highlighted that mouse resting-state functional connectivity converges across centers, although large discrepancies in sensitivity and specificity remained. Here, we explore past and present trends within the animal fMRI community and highlight critical aspects in study design, data acquisition, and post-processing operations, that may affect the results and influence the comparability between studies. We also suggest practices aimed to promote the adoption of standards within the community and improve between-lab reproducibility. The implementation of standardized animal neuroimaging protocols will facilitate animal population imaging efforts as well as meta-analysis and replication studies, the gold standards in evidence-based science.
CRIS-Team Scopus Importer:2020-02-14
Keywords: DREADD; non-human primate; optogenetics; resting-state; rodent

Association of brain functional magnetic resonance activity with response to tumor necrosis factor inhibition in rheumatoid arthritis - Rech, Jürgen; Heß, Andreas; Finzel, Stephanie; Kreitz, Silke; Sergeeva, Marina; Englbrecht, Matthias; Dörfler, Arnd; Saake, Marc; Schett, Georg (Arthritis and Rheumatism, 2013)
Objective To test whether brain activity predicts the response to tumor necrosis factor inhibitors (TNFi) in patients with rheumatoid arthritis (RA). Since clinical and laboratory parameters have proven unsuccessful in predicting response, we followed a radically different concept, hypothesizing that response to TNFi depends on central nervous system activity rather than the clinical signs of disease. Methods Sequential testing by functional magnetic resonance imaging (MRI) of the brain, anatomic MRI of the hand, and clinical assessment of arthritis were carried out in 10 patients with active RA before and 3, 7, and 28 days after the start of TNFi treatment. Results Baseline demographic and disease-specific parameters were identical in TNFi responders and nonresponders. The mean ± SEM decrease in the Disease Activity Score in 28 joints after 28 days was -1.8 ± 0.3 in TNFi responders (n = 5) and -0.2 ± 0.1 in nonresponders (n = 5). Responders showed significantly higher baseline activation in thalamic, limbic, and associative areas of the brain than nonresponders. Moreover, brain activity decreased within 3 days after TNFi exposure in the responders, preceding clinical responses (day 7) and responses observed on the anatomic hand MRI (day 28). Conclusion These data suggest that response to TNFi depends on brain activity in RA patients, reflecting the subjective perception of disease. Copyright © 2013 by the American College of Rheumatology.
CRIS-Team Scopus Importer:2021-02-03

Blockade of TNF-α rapidly inhibits pain responses in the central nervous system - Heß, Andreas; Axmann, Roland; Rech, Jürgen; Finzel, Stephanie; Heindl-Erdmann, Cornelia; Kreitz, Silke; Sergeeva, Marina; Saake, Marc; Garcia, Meritxell; Kollias, George; Straub, Rainer H.; Sporns, Olaf; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2011)
There has been a consistent gap in understanding how TNF-α neutralization affects the disease state of arthritis patients so rapidly, considering that joint inflammation in rheumatoid arthritis is a chronic condition with structural changes. We thus hypothesized that neutralization of TNF-α acts through the CNS before directly affecting joint inflammation. Through use of functional MRI (fMRI), we demonstrate that within 24 h after neutralization of TNF-α, nociceptive CNS activity in the thalamus and somatosensoric cortex, but also the activation of the limbic system, is blocked. Brain areas showing blood-oxygen level-dependent signals, a validated method to assess neuronal activity elicited by pain, were significantly reduced as early as 24 h after an infusion of a monoclonal antibody to TNF-α. In contrast, clinical and laboratory markers of inflammation, such as joint swelling and acute phase reactants, were not affected by anti-TNF-α at these early time points. Moreover, arthritic mice overexpressing human TNF-α showed an altered pain behavior and amore intensive, widespread, and prolonged brain activity upon nociceptive stimuli compared with wild-type mice. Similar to humans, these changes, as well as the rewiring of CNS activity resulting in tight clustering in the thalamus, were rapidly reversed after neutralization of TNF-α. These results suggest that neutralization of TNF-α affects nociceptive brain activity in the context of arthritis, long before it achieves antiinflammatory effects in the joints.
CRIS-Team Scopus Importer:2021-02-03
Keywords: Antiinflammatory therapy; Cytokines

Brain fMRI Predicts Responses to Certolizumab Pegol in RA. an International, Multi-center, Randomized, Double-blind, Placebocontrolled Trial (PreCePRA) - Rech, Jürgen; Schenker, Hannah; Tascilar, Koray; Hagen, Melanie; Kleyer, Arnd; Simon, David; Mendez, Larissa Valor; Schoenau, Verena; Prade, Jutta; Sergeeva, Marina; Sulvakumar, Mageshvar; Strobelt, Sandra; et al. (ARTHRITIS & RHEUMATOLOGY, 2020)
CRIS-Team WoS Importer:2021-01-15

Brain Structure in Acutely Underweight and Partially Weight-Restored Individuals With Anorexia Nervosa: A Coordinated Analysis by the ENIGMA Eating Disorders Working Group - Walton, Esther; Bernardoni, Fabio; Batury, Victoria Luise; Bahnsen, Klaas; Larivière, Sara; Abbate-Daga, Giovanni; Andres-Perpiña, Susana; Bang, Lasse; Bischoff-Grethe, Amanda; Brooks, Samantha J.; Campbell, Iain C.; Cascino, Giammarco; et al. (Biological Psychiatry, 2022)
Background: The pattern of structural brain abnormalities in anorexia nervosa (AN) is still not well understood. While several studies report substantial deficits in gray matter volume and cortical thickness in acutely underweight patients, others find no differences, or even increases in patients compared with healthy control subjects. Recent weight regain before scanning may explain some of this heterogeneity. To clarify the extent, magnitude, and dependencies of gray matter changes in AN, we conducted a prospective, coordinated meta-analysis of multicenter neuroimaging data. Methods: We analyzed T1-weighted structural magnetic resonance imaging scans assessed with standardized methods from 685 female patients with AN and 963 female healthy control subjects across 22 sites worldwide. In addition to a case-control comparison, we conducted a 3-group analysis comparing healthy control subjects with acutely underweight AN patients (n = 466) and partially weight-restored patients in treatment (n = 251). Results: In AN, reductions in cortical thickness, subcortical volumes, and, to a lesser extent, cortical surface area were sizable (Cohen's d up to 0.95), widespread, and colocalized with hub regions. Highlighting the effects of undernutrition, these deficits were associated with lower body mass index in the AN sample and were less pronounced in partially weight-restored patients. Conclusions: The effect sizes observed for cortical thickness deficits in acute AN are the largest of any psychiatric disorder investigated in the ENIGMA (Enhancing Neuro Imaging Genetics through Meta Analysis) Consortium to date. These results confirm the importance of considering weight loss and renutrition in biomedical research on AN and underscore the importance of treatment engagement to prevent potentially long-lasting structural brain changes in this population.
CRIS-Team Scopus Importer:2022-09-09
Keywords: BMI; Cortical thickness; MRI; Subcortical volume; Surface area

Central amygdala circuit dynamics underlying the benzodiazepine anxiolytic effect - Griessner, Johannes; Pasieka, Manuel; Böhm, Vincent; Grössl, Florian; Kaczanowska, Joanna; Pliota, Pinelopi; Kargl, Dominic; Werner, Barbara; Kaouane, Nadia; Strobelt, Sandra; Kreitz, Silke; Heß, Andreas; et al. (Molecular Psychiatry, 2021)
Benzodiazepines (BZDs) have been a standard treatment for anxiety disorders for decades, but the neuronal circuit interactions mediating their anxiolytic effect remain largely unknown. Here, we find that systemic BZDs modulate central amygdala (CEA) microcircuit activity to gate amygdala output. Combining connectome data with immediate early gene (IEG) activation maps, we identified the CEA as a primary site for diazepam (DZP) anxiolytic action. Deep brain calcium imaging revealed that brain-wide DZP interactions shifted neuronal activity in CEA microcircuits. Chemogenetic silencing showed that PKCδ+/SST− neurons in the lateral CEA (CEAl) are necessary and sufficient to induce the DZP anxiolytic effect. We propose that BZDs block the relay of aversive signals through the CEA, in part by local binding to CEAl SST+/PKCδ− neurons and reshaping intra-CEA circuit dynamics. This work delineates a strategy to identify biomedically relevant circuit interactions of clinical drugs and highlights the critical role for CEA circuitry in the pathophysiology of anxiety.
CRIS-Team Scopus Importer:2021-02-12

Central amygdala circuitry modulates nociceptive processing through differential hierarchical interaction with affective network dynamics - Wank, Isabel; Pliota, Pinelopi; Badurek, Sylvia; Kraitsy, Klaus; Kaczanowska, Joanna; Griessner, Johannes; Kreitz, Silke; Heß, Andreas; Haubensak, Wulf (Communications Biology, 2021)
The central amygdala (CE) emerges as a critical node for affective processing. However, how CE local circuitry interacts with brain wide affective states is yet uncharted. Using basic nociception as proxy, we find that gene expression suggests diverging roles of the two major CE neuronal populations, protein kinase C δ-expressing (PKCδ+) and somatostatin-expressing (SST+) cells. Optogenetic (o)fMRI demonstrates that PKCδ+/SST+ circuits engage specific separable functional subnetworks to modulate global brain dynamics by a differential bottom-up vs. top-down hierarchical mesoscale mechanism. This diverging modulation impacts on nocifensive behavior and may underly CE control of affective processing.
CRIS-Team Scopus Importer:2021-06-25

CENTRAL NERVOUS SYSTEM PAIN RESPONSE AND COMPONENTS OF DISEASE ACTIVITY IN RA PATIENTS AFTER TREATMENT WITH CERTOLIZUMAB OR PLACEBO: A POST-HOC ANALYSIS FROM THE PRECEPRA TRIAL - Schenker, Hannah; Rech, Jürgen; Tascilar, K.; Hagen, Melanie; Schoenau, V.; Sergeeva, Marina; Selvakumar, Mageshwar; Konerth, Laura; Prade, Jutta; Strobelt, Sandra; Valor, L.; Hueber, A.; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2020)
CRIS-Team WoS Importer:2020-08-21

Characterization and quantification of angiogenesis in rheumatoid arthritis in a mouse model using ?CT - Gayetskyy, Svitlana; Museyko, Oleg; Käßer, Johannes; Heß, Andreas; Schett, Georg; Engelke, Klaus (BMC Musculoskeletal Disorders, 2014)
Angiogenesis is an important pathophysiological process of chronic inflammation, especially in inflammatory arthritis. Quantitative measurement of changes in vascularization may improve the diagnosis and monitoring of arthritis. The aim of this work is the development of a 3D imaging and analysis framework for quantification of vascularization in experimental arthritis.High-resolution micro-computed tomography (?CT) was used to scan knee joints of arthritic human tumor necrosis factor transgenic (hTNFtg) mice and non-arthritic wild-type controls previously perfused with lead-containing contrast agent Microfil MV-122. Vessel segmentation was performed by combination of intensity-based (local adaptive thresholding) and form-based (multi-scale method) segmentation techniques. Four anatomically defined concentric spherical shells centered in the knee joint were used as analysis volumes of interest. Vessel density, density distribution as well as vessel thickness, surface, spacing and number were measured. Simulated digital vessel tree models were used for validation of the algorithms.High-resolution ?CT allows the quantitative assessment of the vascular tree in the knee joint during arthritis. Segmentation and analysis were highly automated but occasionally required manual corrections of the vessel segmentation close to the bone surfaces. Vascularization was significantly increased in arthritic hTNFtg mice compared to wild type controls. Precision errors for the morphologic parameters were smaller than 3% and 6% for intra- and interoperator analysis, respectively. Accuracy errors for vessel thickness were around 20% for vessels larger than twice the resolution of the scanner.Arthritis-induced changes of the vascular tree, including detailed and quantitative description of the number of vessel branches, length of vessel segments and the bifurcation angle, can be detected by contrast-enhanced high-resolution ?CT.
EVALuna2:8512

Combined resting state-fMRI and calcium recordings show stable brain states for task-induced fMRI in mice under combined ISO/MED anesthesia - Pradier, Bruno; Wachsmuth, Lydia; Nagelmann, Nina; Segelcke, Daniel; Kreitz, Silke; Heß, Andreas; Pogatzki-Zahn, Esther M.; Faber, Cornelius (NeuroImage, 2021)
For fMRI in animal models, the combination of low-dose anesthetic, isoflurane (ISO), and the sedative medetomidine (MED) has recently become an advocated regimen to achieve stable neuronal states and brain networks in rats that are required for reliable task-induced BOLD fMRI. However, in mice the temporal stability of neuronal states and networks in resting-state (rs)-fMRI experiments during the combined ISO/MED regimen has not been systematically investigated. Using a multimodal approach with optical calcium (Ca2+) recordings and rs-fMRI, we investigated cortical neuronal/astrocytic Ca2+activity states and brain networks at multiple time points while switching from anesthesia with 1% ISO to a combined ISO/MED regimen. We found that cortical activity states reached a steady-state 45 min following start of MED infusion as indicated by stable Ca2+ transients. Similarly, rs-networks were not statistically different between anesthesia with ISO and the combined ISO/MED regimen 45 and 100 min after start of MED. Importantly, during the transition time we identified changed rs-network signatures that likely reflect the different mode of action of the respective anesthetic; these included a dose-dependent increase in cortico-cortical functional connectivity (FC) presumably caused by reduction of ISO concentration and decreased FC in subcortical arousal nuclei due to MED infusion. Furthermore, we report detection of visual stimulation-induced BOLD fMRI during the stable ISO/MED neuronal state 45 min after induction. Based on our findings, we recommend a 45-minute waiting period after switching from ISO anesthesia to the combined ISO/MED regimen before performing rs- or task-induced fMRI experiments.
CRIS-Team Scopus Importer:2021-10-29
Keywords: Anesthesia; Brain state; Graph theory; Mouse; Resting-state fMRI; Task-induced fMRI

Common functional networks in the mouse brain revealed by multi-centre resting-state fMRI analysis - Grandjean, Joanes; Canella, Carola; Anckaerts, Cynthia; Ayrancı, Gülebru; Bougacha, Salma; Bienert, Thomas; Buehlmann, David; Coletta, Ludovico; Gallino, Daniel; Gass, Natalia; Garin, Clément M.; Nadkarni, Nachiket Abhay; et al. (NeuroImage, 2020)
Preclinical applications of resting-state functional magnetic resonance imaging (rsfMRI) offer the possibility to non-invasively probe whole-brain network dynamics and to investigate the determinants of altered network signatures observed in human studies. Mouse rsfMRI has been increasingly adopted by numerous laboratories worldwide. Here we describe a multi-centre comparison of 17 mouse rsfMRI datasets via a common image processing and analysis pipeline. Despite prominent cross-laboratory differences in equipment and imaging procedures, we report the reproducible identification of several large-scale resting-state networks (RSN), including a mouse default-mode network, in the majority of datasets. A combination of factors was associated with enhanced reproducibility in functional connectivity parameter estimation, including animal handling procedures and equipment performance. RSN spatial specificity was enhanced in datasets acquired at higher field strength, with cryoprobes, in ventilated animals, and under medetomidine-isoflurane combination sedation. Our work describes a set of representative RSNs in the mouse brain and highlights key experimental parameters that can critically guide the design and analysis of future rodent rsfMRI investigations.
CRIS-Team Scopus Importer:2019-10-29
Keywords: Connectome; Default-mode network; Functional connectivity; ICA; Seed-based

Comparing brain activity patterns during spontaneous exploratory and cue-instructed learning using single photon-emission computed tomography (SPECT) imaging of regional cerebral blood flow in freely behaving rats - Mannewitz, A.; Bock, J.; Kreitz, Silke; Heß, Andreas; Goldschmidt, J.; Scheich, H.; Braun, Katharina (Brain Structure & Function, 2018)
Learning can be categorized into cue-instructed and spontaneous learning types; however, so far, there is no detailed comparative analysis of specific brain pathways involved in these learning types. The aim of this study was to compare brain activity patterns during these learning tasks using the in vivo imaging technique of single photon-emission computed tomography (SPECT) of regional cerebral blood flow (rCBF). During spontaneous exploratory learning, higher levels of rCBF compared to cue-instructed learning were observed in motor control regions, including specific subregions of the motor cortex and the striatum, as well as in regions of sensory pathways including olfactory, somatosensory, and visual modalities. In addition, elevated activity was found in limbic areas, including specific subregions of the hippocampal formation, the amygdala, and the insula. The main difference between the two learning paradigms analyzed in this study was the higher rCBF observed in prefrontal cortical regions during cue-instructed learning when compared to spontaneous learning. Higher rCBF during cue-instructed learning was also observed in the anterior insular cortex and in limbic areas, including the ectorhinal and entorhinal cortexes, subregions of the hippocampus, subnuclei of the amygdala, and the septum. Many of the rCBF changes showed hemispheric lateralization. Taken together, our study is the first to compare partly lateralized brain activity patterns during two different types of learning.
EVALuna2:214359

Contribution of Inflammation and Bone Destruction to Pain in Arthritis: A Study in Murine Glucose-6-Phosphate Isomerase–Induced Arthritis - Ebbinghaus, Matthias; Müller, Sylvia; Segond von Banchet, Gisela; Eitner, Annett; Wank, Isabel; Heß, Andreas; Hilger, Ingrid; Kamradt, Thomas; Schaible, Hans Georg (Arthritis and Rheumatology, 2019)
Objective: Arthritis is often characterized by inflammation and bone destruction. This study was undertaken to investigate the contribution of inflammation and bone destruction to pain. Methods: Inflammation, bone resorption, pain-related behaviors, and molecular markers (activating transcription factor 3 [ATF-3], p-CREB, and transient receptor potential vanilloid channel 1) in sensory neurons were measured in murine glucose-6-phosphate isomerase (G6PI)–induced arthritis, a model of rheumatoid arthritis. Depletion of Treg cells before immunization changed self-limiting arthritis into nonremitting arthritis with pronounced bone destruction. Zoledronic acid (ZA) was administered to reduce bone resorption. Results: Compared to nondepleted mice, Treg cell–depleted mice exhibited arthritis with more severe bone destruction and higher guarding scores (P < 0.05; n = 10 mice per group) as well as more persistent thermal hyperalgesia (P < 0.05), but displayed similar mechanical hyperalgesia at the hindpaws (n = 18–26 mice per group). These pain-related behaviors, as well as an up-regulation of the neuronal injury marker ATF-3 in sensory neurons (studied in 39 mice), appeared before the clinical score (inflammation) became positive and persisted in Treg cell–depleted and nondepleted mice. In the late stage of arthritis, Treg cell–depleted mice treated with ZA showed less bone resorption (<50%; P < 0.01) and less thermal hyperalgesia (P < 0.01) than Treg cell–depleted mice without ZA treatment (n = 15 mice per group), but ZA treatment did not reduce the clinical score and local mechanical hyperalgesia. Conclusion: Pain-related behaviors precede and outlast self-limiting arthritis. In nonremitting arthritis with enhanced bone destruction, mainly local thermal, but not local mechanical, hyperalgesia was aggravated. The up-regulation of ATF-3 indicates an early and persisting affection of sensory neurons by G6PI-induced arthritis.
CRIS-Team Scopus Importer:2019-11-19

Definition of K(trans) and FA Thresholds for Better Assessment of Experimental Glioma Using High-field MRI: A Feasibility Study - Engelhorn, Tobias; Schwarz, Martin; Heß, Andreas; Budinsky, Lubos; Pitann, Patrick; Eyüpoglu, Ilker Yasin; Dörfler, Arnd (Clinical Neuroradiology, 2014)
To define K(trans) and fractional anisotropy (FA) thresholds in correlation to histology for improved magnetic resonance imaging (MRI) tumor assessment in an animal model of brain glioma.Twelve rats underwent 4.7 T MRI at day 10 after tumor implantation. Anatomical scans (T2, T1 at 8 min after double dose contrast application) as well as dynamic contrast-enhanced (DCE) imaging with calculation of K(trans) and diffusion tensor imaging (DTI) with calculation of FA were performed. T2- and T1-derived tumor volumes were calculated and thresholds for K(trans) and FA were defined for best MRI tumor assessment correlated to histology.Tumor volumes were 159 ± 14 mm(3) (histology), 126 ± 26 mm(3) (T1 with contrast, r = 0.76), and 153 ± 12 mm(3) (T2, r = 0.84), respectively. K(trans)- and FA-derived tumor volumes were 160 ± 16 mm(3) (for K(trans) ³ 0.04 min(-1), r = 0.94), and 159 ± 14 mm(3) (for FA £ 0.14, r = 0.96), respectively.DCE-MRI and DTI with calculation of K(trans) and FA maps allow very precise brain glioma assessment comparable to histology if established thresholds for the given tumor model are used.
EVALuna2:8504

Diagnostic imaging in cancer therapy with magnetic nanoparticles - Lyer, Stefan; Tietze, Rainer; Dürr, Stephan; Struffert, Tobias; Engelhorn, Tobias Martin; Schwarz, Marc; Dörfler, Arnd; Budinsky, Lubos; Heß, Andreas; Schmidt, Wolfgang; Jurgons, Roland; Alexiou, Christoph (Springer Proceedings in Physics, 2012)
The unfavorable application-to-tumor-dose-ratio is a drawback of conventional systemic chemotherapy, implying an often insufficient drug dose in the tumor being associated with severe side effects for the patient. The use of chemotherapeutics bound to magnetic nanoparticles offers several advantages. On the one hand it is possible to concentrate the chemotherapeutics in the tumor region by the use of magnetic fields, like it is done in Magnetic Drug Targeting (MDT). On the other hand magnetic particles can serve as contrast agent for magnetic resonance imaging (MRI) that is bound to the therapeutics. Hence, the particles possibly are opening an insight into drug distribution in the tumor region directly after administration. Another important factor for a successful MDT-application is detailed knowledge about tumor vascularization. In this pilot study we investigated vascularization and size of an tumor in an experimental in vivo tumor model via flat-panel angiography and DYNA-CT before MDT and the particle distribution with MRI after MDT. We could show that the tumor could be displayed by MRI and DYNA-CT before and after MDT. Flat panel angiography revealed clearly the pathological tumor vascularization before MDT, while MRI imaging afterwards displayed the tumor as well as the particle distribution in the tumor.
CRIS-Team Scopus Importer:2022-06-27
Keywords: Magnetic Nanoparticles; Tumor Region; Magnetic Resonance Imaging Imaging; Signal Extinction; Left Hind Limb

Disentangling the impact of cerebrospinal fluid formation and neuronal activity on solute clearance from the brain - Segeroth, Martin; Wachsmuth, Lydia; Gagel, Mathias; Albers, Franziska; Heß, Andreas; Faber, Cornelius (Fluids and Barriers of the CNS, 2023)
Background: Despite recent attention, pathways and mechanisms of fluid transposition in the brain are still a matter of intense discussion and driving forces underlying waste clearance in the brain remain elusive. Consensus exists that net solute transport is a prerequisite for efficient clearance. The individual impact of neuronal activity and cerebrospinal fluid (CSF) formation, which both vary with brain state and anesthesia, remain unclear. Methods: To separate conditions with high and low neuronal activity and high and low CSF formation, different anesthetic regimens in naive rat were established, using Isoflurane (ISO), Medetomidine (MED), acetazolamide or combinations thereof. With dynamic contrast-enhanced MRI, after application of low molecular weight contrast agent (CA) Gadobutrol to cisterna magna, tracer distribution was monitored as surrogate for solute clearance. Simultaneous fiber-based Ca2+-recordings informed about the state of neuronal activity under different anesthetic regimen. T2-weighted MRI and diffusion-weighted MRI (DWI) provided size of subarachnoidal space and aqueductal flow as surrogates for CSF formation. Finally, a pathway and mechanism-independent two-compartment model was introduced to provide a measure of efficiency for solute clearance from the brain. Results: Anatomical imaging, DWI and Ca2+-recordings confirmed that conditions with distinct levels of neuronal activity and CSF formation were achieved. A sleep-resembling condition, with reduced neuronal activity and enhanced CSF formation was achieved using ISO+MED and an awake-like condition with high neuronal activity using MED alone. CA distribution in the brain correlated with the rate of CSF formation. The cortical brain state had major influence on tracer diffusion. Under conditions with low neuronal activity, higher diffusivity suggested enlargement of extracellular space, facilitating a deeper permeation of solutes into brain parenchyma. Under conditions with high neuronal activity, diffusion of solutes into parenchyma was hindered and clearance along paravascular pathways facilitated. Exclusively based on the measured time signal curves, the two-compartment model provided net exchange ratios, which were significantly larger for the sleep-resembling condition than for the awake-like condition. Conclusions: Efficiency of solute clearance in brain changes with alterations in both state of neuronal activity and CSF formation. Our clearance pathway and mechanism agnostic kinetic model informs about net solute transport, solely based on the measured time signal curves. This rather simplifying approach largely accords with preclinical and clinical findings.
CRIS-Team Scopus Importer:2023-06-30
Keywords: Brain state; Ca; CSF production; DCE MRI; DWI; Glymphatic system; Kinetic modeling; Solute clearance

Distinct functional cerebral hypersensitivity networks during incisional and inflammatory pain in rats - Kreitz, Silke; Pradier, Bruno; Segelcke, Daniel; Amirmohseni, Saeedeh; Heß, Andreas; Faber, Cornelius; Pogatzki-Zahn, Esther M. (Current Research in Neurobiology, 2025)
Although the pathophysiology of pain has been investigated tremendously, there are still many open questions with regard to specific pain entities and their pain-related symptoms. To increase the translational impact of (preclinical) animal neuroimaging pain studies, the use of disease-specific pain models, as well as relevant stimulus modalities, are critical. We developed a comprehensive framework for brain network analysis combining functional magnetic resonance imaging (MRI) with graph-theory (GT) and data classification by linear discriminant analysis. This enabled us to expand our knowledge of stimulus modalities processing under incisional (INC) and pathogen-induced inflammatory (CFA) pain entities compared to acute pain conditions. GT-analysis has uncovered specific features in pain modality processing that align well with those previously identified in humans. These include areas such as S1, M1, CPu, HC, piriform, and cingulate cortex. Additionally, we have identified unique Network Signatures of Pain Hypersensitivity (NSPH) for INC and CFA. This leads to a diminished ability to differentiate between stimulus modalities in both pain models compared to control conditions, while also enhancing aversion processing and descending pain modulation. Our findings further show that different pain entities modulate sensory input through distinct NSPHs. These neuroimaging signatures are an important step toward identifying novel cerebral pain biomarkers for certain diseases and relevant outcomes to evaluate target engagement of novel therapeutic and diagnostic options, which ultimately can be translated to the clinic.
CRIS-Team Scopus Importer:2025-02-17
Keywords: Animal neuroimaging studies; Cerebral pain biomarkers; Disease-specific pain models; Functional MRI (fMRI); Graph theory in pain analysis; Incisional pain (INC); Inflammatory pain (CFA); Linear discriminant analysis; Network signatures of pain hypersensitivity (NSPH); Pain pathophysiology

Editorial: Status Go for Preclinical Imaging - Kuntner, Claudia; Baumann, Bernhard; Tavares, Adriana A. S.; Heß, Andreas (Frontiers in Physics, 2020)
CRIS-Team Scopus Importer:2020-10-30
Keywords: microscopy; MRI; PET; preclinical imaging; quantification; SPECT; ultrasound

EFhd2/Swiprosin-1 is a common genetic determinator for sensation-seeking/low anxiety and alcohol addiction - Mielenz, Dirk; Reichel, Martin; Jia, T.; Quinlan, E. B.; Stöckl, Thomas; Mettang, M.; Zilske, Daniel; Kirmizi Alsan, Elif; Schoenberger, P.; Praetner, M.; Huber, Sabine; Amato, Davide; et al. (Molecular Psychiatry, 2017)
In many societies, the majority of adults regularly consume alcohol. However, only a small proportion develops alcohol addiction. Individuals at risk often show a high sensation-seeking/low-anxiety behavioural phenotype. Here we asked which role EF hand domain containing 2 (EFhd2; Swiprosin-1) plays in the control of alcohol addiction-associated behaviours. EFhd2 knockout (KO) mice drink more alcohol than controls and spontaneously escalate their consumption. This coincided with a sensation-seeking and low-anxiety phenotype. A reversal of the behavioural phenotype with β-carboline, an anxiogenic inverse benzodiazepine receptor agonist, normalized alcohol preference in EFhd2 KO mice, demonstrating an EFhd2-driven relationship between personality traits and alcohol preference. These findings were confirmed in a human sample where we observed a positive association of the EFhd2 single-nucleotide polymorphism rs112146896 with lifetime drinking and a negative association with anxiety in healthy adolescents. The lack of EFhd2 reduced extracellular dopamine levels in the brain, but enhanced responses to alcohol. In confirmation, gene expression analysis revealed reduced tyrosine hydroxylase expression and the regulation of genes involved in cortex development, Eomes and Pax6, in EFhd2 KO cortices. These findings were corroborated in Xenopus tadpoles by EFhd2 knockdown. Magnetic resonance imaging (MRI) in mice showed that a lack of EFhd2 reduces cortical volume in adults. Moreover, human MRI confirmed the negative association between lifetime alcohol drinking and superior frontal gyrus volume. We propose that EFhd2 is a conserved resilience factor against alcohol consumption and its escalation, working through Pax6/Eomes. Reduced EFhd2 function induces high-risk personality traits of sensation-seeking/low anxiety associated with enhanced alcohol consumption, which may be related to cortex function.
EVALuna2:4036

Engineering of vascularized transplantable bone tissues: induction of axial vascularization in an osteoconductive matrix using an arteriovenous loop. - Kneser, Ulrich; Polykandriotis, Elias; Ohnolz, Jan; Heidner, Kristina; Grabinger, Lucia; Euler, Simon; Amann, Kerstin Ute; Heß, Andreas; Brune, Kay; Greil, Peter; Stürzl, Michael; Horch, Raymund E. (Tissue Engineering -Larchmont, 2006)
This study demonstrates for the first time successful vascularization of solid porous matrices by means of an AV loop. Injection of osteogenic cells into axially prevascularized matrices may eventually create functional bioartificial bone tissues for reconstruction of large defects. Vascularization remains an obstacle to engineering of larger volume bone tissues. Our aim was to induce axial vascularization in a processed bovine cancellous bone (PBCB) matrix using an arteriovenous (AV) loop (artery, vein graft, and vein). Custom-made PBCB discs (9 x 5 mm) were implanted into rats. In group A (n = 19), the matrices were inserted into microsurgically constructed AV loops between the femoral vessels using a vein graft from the contralateral side. In group B (n = 19), there was no vascular carrier. The matrices were encased in isolation chambers. After 2, 4, and 8 weeks, the animals were perfused with India ink via the abdominal aorta. Matrices were explanted and subjected to histological and morphometric analysis. Results were compared with intravital dynamic micro & magnetic resonance imaging and scanning electron microscopy images of vascular corrosion replicas. In group A, significant vascularization of the matrix had occurred by the 8th week. At this time, vascular remodeling with organization into vessels of different sizes was evident. Blood vessels originated from all 3 zones of the AV loop. Group A was significantly superior to group B in terms of vascular density and vascularization kinetics. DISCUSSION INTRODUCTION METHODS RESULTS

Epilepsy-related functional brain network alterations are already present at an early age in the GAERS rat model of genetic absence epilepsy - Wachsmuth, Lydia; Hebbelmann, Leo; Prade, Jutta; Kohnert, Laura C.; Lambers, Henriette; Lüttjohann, Annika; Budde, Thomas; Heß, Andreas; Faber, Cornelius (Frontiers in Neurology, 2024)
Introduction: Genetic Absence Epilepsy Rats from Strasbourg (GAERS) represent a model of genetic generalized epilepsy. The present longitudinal study in GAERS and age-matched non-epileptic controls (NEC) aimed to characterize the epileptic brain network using two functional measures, resting state-functional magnetic resonance imaging (rs-fMRI) and manganese-enhanced MRI (MEMRI) combined with morphometry, and to investigate potential brain network alterations, following long-term seizure activity. Methods: Repeated rs-fMRI measurements at 9.4 T between 3 and 8 months of age were combined with MEMRI at the final time point of the study. We used graph theory analysis to infer community structure and global and local network parameters from rs-fMRI data and compared them to brain region-wise manganese accumulation patterns and deformation-based morphometry (DBM). Results: Functional connectivity (FC) was generally higher in GAERS when compared to NEC. Global network parameters and community structure were similar in NEC and GAERS, suggesting efficiently functioning networks in both strains. No progressive FC changes were observed in epileptic animals. Network-based statistics (NBS) revealed stronger FC within the cortical community, including regions of association and sensorimotor cortex, and with basal ganglia and limbic regions in GAERS, irrespective of age. Higher manganese accumulation in GAERS than in NEC was observed at 8 months of age, consistent with higher overall rs-FC, particularly in sensorimotor cortex and association cortex regions. Functional measures showed less similarity in subcortical regions. Whole brain volumes of 8 months-old GAERS were higher when compared to age-matched NEC, and DBM revealed increased volumes of several association and sensorimotor cortex regions and of the thalamus. Discussion: rs-fMRI, MEMRI, and volumetric data collectively suggest the significance of cortical networks in GAERS, which correlates with an increased fronto-central connectivity in childhood absence epilepsy (CAE). Our findings also verify involvement of basal ganglia and limbic regions. Epilepsy-related network alterations are already present in juvenile animals. Consequently, this early condition seems to play a greater role in dynamic brain function than chronic absence seizures.
CRIS-Team Scopus Importer:2024-03-29
Keywords: absence epilepsy; deformation-based morphometry; functional connectivity; GAERS; graph theory; MEMRI; rs-fMRI; spike–wave-discharges

Fat/carbohydrate ratio but not energy density determines snack food intake and activates brain reward areas - Hoch, Tobias; Kreitz, Silke; Gaffling, Simone; Pischetsrieder, Monika; Heß, Andreas (Scientific Reports, 2015)
The snack food potato chips induces food intake in ad libitum fed rats, which is associated with modulation of the brain reward system and other circuits. Here, we show that food intake in satiated rats is triggered by an optimal fat/carbohydrate ratio. Like potato chips, an isocaloric fat/carbohydrate mixture influenced whole brain activity pattern of rats, affecting circuits related e.g. to reward/addiction, but the number of modulated areas and the extent of modulation was lower compared to the snack food itself.
UnivIS-Import:2015-07-08:Pub.2015.nat.dchph.llmch.fatcar

Functional Brain Imaging Reveals Rapid Blockade of Abdominal Pain Response Upon Anti-TNF Therapy in Crohn's Disease - Heß, Andreas; Roesch, Julie; Saake, Marc; Sergeeva, Marina; Hirschmann, Simon; Neumann, Helmut; Dörfler, Arnd; Neurath, Markus; Atreya, Raja (Gastroenterology, 2015)
EVALuna2:2003

HCN2 channels account for mechanical (but not heat) hyperalgesia during long-standing inflammation - Schnorr, Sabine; Eberhardt, Mirjam; Kistner, Katrin; Rajab, Hamsa; Kaesser, Johannes; Heß, Andreas; Reeh, Peter; Ludwig, Andreas; Herrmann, Stefan (Pain, 2014)
There is emerging evidence that hyperpolarization-activated cation (HCN) channels are involved in the development of pathological pain, including allodynia and hyperalgesia. Mice lacking the HCN isoform 2 display reduced heat but unchanged mechanical pain behavior, as recently shown in preclinical models of acute inflammatory pain. However, the impact of HCN2 to chronic pain conditions is less clear and has not been examined so far. In this report, we study the role of HCN2 in the complete Freund's adjuvant inflammation model reflecting chronic pain conditions. We used sensory neuron-specific as well as inducible global HCN2 mutants analyzing pain behavior in persistent inflammation and complemented this by region-specific administration of an HCN channel blocker. Our results demonstrate that the absence of HCN2 in primary sensory neurons reduces tactile hypersensitivity in chronic inflammatory conditions but leaves heat hypersensitivity unaffected. This result is in remarkable contrast to the recently described role of HCN2 in acute inflammatory conditions. We show that chronic inflammation results in an increased expression of HCN2 and causes sensitization in peripheral and spinal terminals of the pain transduction pathway. The contribution of HCN2 to peripheral sensitization mechanisms was further supported by single-fiber recordings from isolated skin-nerve preparations and by conduction velocity measurements of saphenous nerve preparations. Global HCN2 mutants revealed that heat hypersensitivity-unaffected in peripheral HCN2 mutants-was diminished by the additional disruption of central HCN2 channels, suggesting that thermal hyperalgesia under chronic inflammatory conditions is mediated by HCN2 channels beyond primary sensory afferents.
EVALuna2:2422

Human CLP1 mutations alter tRNA biogenesis, affecting both peripheral and central nervous system function - Karaca, Ender; Weitzer, Stefan; Pehlivan, Davut; Shiraishi, Hiroshi; Gogakos, Tasos; Hanada, Toshikatsu; Jhangiani, Shalini N.; Wiszniewski, Wojciech; Withers, Marjorie; Campbell, Ian M.; Erdin, Serkan; Isikay, Sedat; et al. (Cell, 2014)
CLP1 is a RNA kinase involved in tRNA splicing. Recently, CLP1 kinase-dead mice were shown to display a neuromuscular disorder with loss of motor neurons and muscle paralysis. Human genome analyses now identified a CLP1 homozygous missense mutation (p.R140H) in five unrelated families, leading to a loss of CLP1 interaction with the tRNA splicing endonuclease (TSEN) complex, largely reduced pre-tRNA cleavage activity, and accumulation of linear tRNA introns. The affected individuals develop severe motor-sensory defects, cortical dysgenesis, and microcephaly. Mice carrying kinase-dead CLP1 also displayed microcephaly and reduced cortical brain volume due to the enhanced cell death of neuronal progenitors that is associated with reduced numbers of cortical neurons. Our data elucidate a neurological syndrome defined by CLP1 mutations that impair tRNA splicing. Reduction of a founder mutation to homozygosity illustrates the importance of rare variations in disease and supports the clan genomics hypothesis.
EVALuna2:8517

Imaging of Functional Brain Circuits during Acquisition and Memory Retrieval in an Aversive Feedback Learning Task: Single Photon Emission Computed Tomography of Regional Cerebral Blood Flow in Freely Behaving Rats - Braun, Katharina; Mannewitz, Anja; Bock, Joerg; Kreitz, Silke; Heß, Andreas; Scheich, Henning; Goldschmidt, Juergen (Brain Sciences, 2021)
Active avoidance learning is a complex form of aversive feedback learning that in humans and other animals is essential for actively coping with unpleasant, aversive, or dangerous situations. Since the functional circuits involved in two-way avoidance (TWA) learning have not yet been entirely identified, the aim of this study was to obtain an overall picture of the brain circuits that are involved in active avoidance learning. In order to obtain a longitudinal assessment of activation patterns in the brain of freely behaving rats during different stages of learning, we applied single-photon emission computed tomography (SPECT). We were able to identify distinct prefrontal cortical, sensory, and limbic circuits that were specifically recruited during the acquisition and retrieval phases of the two-way avoidance learning task.
CRIS-Team WoS Importer:2021-06-04

Imaging the influence of peripheral TRPV1-signaling on cerebral nociceptive processing applying fMRI-based graph theory in a resiniferatoxin rat model - Wank, Isabel; Kutsche, Lisa; Kreitz, Silke; Reeh, Peter; Heß, Andreas (PLoS ONE, 2022)
Resiniferatoxin (RTX), an extract from the spurge plant Euphorbia resinifera, is a potent agonist of the transient receptor potential cation channel subfamily V member 1 (TRPV1), mainly expressed on peripheral nociceptors—a prerequisite for nociceptive heat perception. Systemic overdosing of RTX can be used to desensitize specifically TRPV1-expressing neurons, and was therefore utilized here to selectively characterize the influence of TRPV1-signaling on central nervous system (CNS) temperature processing. Resting state and CNS temperature processing of male rats were assessed via functional magnetic resonance imaging before and after RTX injection. General linear model-based and graph-theoretical network analyses disentangled the underlying distinct CNS circuitries. At baseline, rats displayed an increase of nociception-related response amplitude and activated brain volume that correlated highly with increasing stimulation temperatures. In contrast, RTX-treated rats showed a clear disruption of thermal nociception, reflected in a missing increase of CNS responses to temperatures above 48°C. Graph-theoretical analyses revealed two distinct brain subnetworks affected by RTX: one subcortical (brainstem, lateral and medial thalamus, hippocampus, basal ganglia and amygdala), and one cortical (primary sensory, motor and association cortices). Resting state analysis revealed first, that peripheral desensitization of TRPV1-expressing neurons did not disrupt the basic resting-state-network of the brain. Second, only at baseline, but not after RTX, noxious stimulation modulated the RS-network in regions associated with memory formation (e.g. hippocampus). Altogether, the combination of whole-brain functional magnetic resonance imaging and RTX-mediated desensitization of TRPV1-signaling provided further detailed insight into cerebral processing of noxious temperatures.
CRIS-Team Scopus Importer:2022-05-20

Impaired maturation of resting-state connectivity in anorexia nervosa from adolescence to adulthood: differential mechanisms of consummatory vs. anticipatory responses through a symptom provocation paradigm - Mendez Torrijos, Andrea; Selvakumar, Mageshwar; Kreitz, Silke; Rösch, Julie; Dörfler, Arnd; Paslakis, Georgios; Krehbiel, Johannes; Steins-Löber, Sabine; Kratz, Oliver; Horndasch, Stefanie; Heß, Andreas (Frontiers in Behavioral Neuroscience, 2024)
This functional magnetic resonance imaging (fMRI) study examined resting-state (RS) connectivity in adolescent and adult patients with anorexia nervosa (AN) using symptom provocation paradigms. Differential food reward mechanisms were investigated through separate assessments of responses to food images and low-caloric/high-caloric food consumption. Thirteen young (≤ 21 years) and seventeen adult (> 21 years) patients with AN and age-matched controls underwent two stimulus-driven fMRI sessions involving RS scans before and after the presentation of food-related stimuli and food consumption. Graph theory and machine learning were used for analyzing the fMRI and clinical data. Healthy controls (HCs) showed widespread developmental changes, while young participants with AN exhibited cerebellum differences for high-calorie food. Young individuals with AN displayed increased connectivity during the consumption of potato chips compared to zucchini, with no differences in adults with AN. Multiparametric machine learning accurately distinguished young individuals with AN from healthy controls based on RS connectivity following food visual stimulation (“anticipatory”) and consumption (“consummatory”). This study highlights the differential food reward mechanisms and minimal developmental changes in RS connectivity from youth to adulthood in individuals with AN compared to healthy controls. Young individuals with AN demonstrated heightened reactivity to high-caloric foods, while adults showed decreased responsiveness, potentially due to desensitization. These findings shed light on aberrant eating behaviors in individuals with AN and contribute to our understanding of the chronicity of the disease.
CRIS-Team Scopus Importer:2024-11-22
Keywords: anorexia nervosa; brain development; fMRI; food intake; graph-theory; machine learning; snack food

Increased bone density and resistance to ovariectomy-induced bone loss in FoxP3-transgenic mice based on impaired osteoclast differentiation. - Zaiss, Mario; Sarter, Kerstin; Heß, Andreas; Engelke, Klaus; Boehm, Christina; Nimmerjahn, Falk; Voll, Reinhard; Schett, Georg; David, Jean-Pierre (Arthritis and Rheumatism, 2010)
OBJECTIVE Immune activation triggers bone loss. Activated T cells are the cellular link between immune activation and bone destruction. The aim of this study was to determine whether immune regulatory mechanisms, such as naturally occurring Treg cells, also extend their protective effects to bone homeostasis in vivo. METHODS Bone parameters in FoxP3-transgenic (Tg) mice were compared with those in their wild-type (WT) littermate controls. Ovariectomy was performed in FoxP3-Tg mice as a model of postmenopausal osteoporosis, and the bone parameters were analyzed. The bones of RAG-1(-/-) mice were analyzed following the adoptive transfer of isolated CD4+CD25+ T cells. CD4+CD25+ T cells and CD4+ T cells isolated from FoxP3-Tg mice and WT mice were cocultured with monocytes to determine their ability to suppress osteoclastogenesis in vitro. RESULTS FoxP3-Tg mice developed higher bone mass and were protected from ovariectomy-induced bone loss. The increase in bone mass was found to be the result of impaired osteoclast differentiation and bone resorption in vivo. Bone formation was not affected. Adoptive transfer of CD4+CD25+ T cells into T cell-deficient RAG-1(-/-) mice also increased the bone mass, indicating that Treg cells directly affect bone homeostasis without the need to engage other T cell lineages. CONCLUSION These data demonstrate that Treg cells can control bone resorption in vivo and can preserve bone mass during physiologic and pathologic bone remodeling.

Influence of the fat/carbohydrate component of snack food on energy intake pattern and reinforcing properties in rodents - Heß, Andreas; Kreß, Stefanie; Rakete, Stefan; Muench, Gerald; Kornhuber, Johannes; Pischetsrieder, Monika; Müller, Christian P. (Behavioural Brain Research, 2019)
Hedonic intake of strongly rewarding foods is independent from biological needs and, thus, a common cause of obesity. The effect of potato chips on energy intake in a snacking model could be explained by their fat/carbohydrate content (FCHc). The present study investigated if the FCHc shapes energy intake patterns and reward processing of satiated rodents. Modulation of energy intake patterns was studied in an established snacking model offering FCHc rich food for 3 x 10 min/day to satiated rats. Reward processing was analyzed by a previously established conditioned place preference tests in satiated mice. The limited access to FCHc rich food led to higher daily energy intake compared to days without access (110 +/- 10 vs. 96 +/- 5 kcal/day) indicating that fat/carbohydrate intake was not fully compensated by reducing standard chow intake during the rest of the day. Furthermore, fat/carbohydrate snacking led to binge eating episodes with up to 55% of the daily energy intake consumed during limited access. Forced withdrawal from fat/carbohydrate snacking opportunities for six weeks increased the total daily energy intake and the relative amount of energy consumed by FCHc after reintroducing fat/carbohydrate snacking. Snack food and fat/carbohydrate food were powerful food reinforcers in satiated mice in contrast to standard chow. Altogether, these data suggest that the FCHc of snack food has strong reinforcing properties, which are probably responsible for the significant modulation of the amount and pattern of food intake in ad libitum fed animals.
CRIS-Team WoS Importer:2019-04-16

Influence of the Peripheral Nervous System on Murine Osteoporotic Fracture Healing and Fracture-Induced Hyperalgesia - Wank, Isabel; Niedermair, Tanja; Kronenberg, Daniel; Stange, Richard; Brochhausen, Christoph; Heß, Andreas; Graessel, Susanne (International Journal of Molecular Sciences, 2023)
Osteoporotic fractures are often linked to persisting chronic pain and poor healing outcomes. Substance P (SP), alpha-calcitonin gene-related peptide (alpha-CGRP) and sympathetic neurotransmitters are involved in bone remodeling after trauma and nociceptive processes, e.g., fracture-induced hyperalgesia. We aimed to link sensory and sympathetic signaling to fracture healing and fracture-induced hyperalgesia under osteoporotic conditions. Externally stabilized femoral fractures were set 28 days after OVX in wild type (WT), alpha-CGRP- deficient (alpha-CGRP -/-), SP-deficient (Tac1-/-) and sympathectomized (SYX) mice. Functional MRI (fMRI) was performed two days before and five and 21 days post fracture, followed by mu CT and biomechanical tests. Sympathectomy affected structural bone properties in the fracture callus whereas loss of sensory neurotransmitters affected trabecular structures in contralateral, non-fractured bones. Biomechanical properties were mostly similar in all groups. Both nociceptive and resting-state (RS) fMRI revealed significant baseline differences in functional connectivity (FC) between WT and neurotransmitter-deficient mice. The fracture-induced hyperalgesia modulated central nociception and had robust impact on RS FC in all groups. The changes demonstrated in RS FC in fMRI might potentially be used as a bone traumata-induced biomarker regarding fracture healing under pathophysiological musculoskeletal conditions. The findings are of clinical importance and relevance as they advance our understanding of pain during osteoporotic fracture healing and provide a potential imaging biomarker for fracture-related hyperalgesia and its temporal development. Overall, this may help to reduce the development of chronic pain after fracture thereby improving the treatment of osteoporotic fractures.
CRIS-Team WoS Importer:2023-02-03

Insights into the infiltrative behavior of adamantinomatous craniopharyngioma in a new xenotransplant mouse model - Stache, Christina; Hoelsken, Annett; Schlaffer, Sven-Martin; Heß, Andreas; Metzler, Markus; Frey, Benjamin; Fahlbusch, Rudolf; Flitsch, Joerg; Buchfelder, Michael; Buslei, Rolf (Brain Pathology, 2015)
Adamantinomatous craniopharyngiomas (adaCP) cause hypothalamic pituitary dysfunction. Elucidation of pathomechanisms underlying tumor progression is essential for the development of targeted chemotherapeutic treatment options. In order to study the mechanisms of tumor outgrowth, we implanted human primary adaCP tissue from three different surgical specimens stereotactically into the brain of immunodeficient mice (n = 20). Three months after tumor inoculation, magnetic resonance imaging and histology confirmed tumor engraftment in all 20 mice (100%) that obtained tissue transplants. The lesions invaded adjoining brain tissue with micro finger-shaped protrusions. Immunohistochemical comparison of the primary tumor and xenotransplants revealed a similar amount of proliferation (Mib-1) and cytokeratin expression pattern (KL-1). Whole tumor reconstruction using serial sections confirmed whirl-like cell clusters with nuclear ?-catenin accumulations at the tumor brain border. These whirls were surrounded by a belt of Claudin-1 expressing cells, showed an activated epidermal growth factor receptor (EGFR) and distinct CD133 as well as p21(WAF1/Cip1) positivity, indicating a tumor stem cell phenotype. Consistent with our previous in vitro studies, intracranial xenotransplants of adaCP confirmed cells with nuclear ?-catenin and activated EGFR being the driving force of tumor outgrowth. This model provides the possibility to study in vivo tumor cell migration and to test novel treatment regimens targeting this tumor stem cell niche.
EVALuna2:7210

In-Vivo Imaging of Cell Migration Using Contrast Enhanced MRI and SVM Based Post-Processing - Weis, Christian; Heß, Andreas; Budinsky, Lubos; Fabry, Ben (PLoS ONE, 2015)

Learning from a Handful Volumes: MRI Resolution Enhancement with Volumetric Super-Resolution Forests - Sindel, Aline; Breininger, Katharina; Käßer, Johannes; Heß, Andreas; Maier, Andreas; Köhler, Thomas (25th IEEE International Conference on Image Processing, ICIP 2018, 2018)
Magnetic resonance imaging (MRI) enables 3-D imaging of anatomical structures. However, the acquisition of MR volumes with high spatial resolution leads to long scan times. To this end, we propose volumetric super-resolution forests (VSRF) to enhance MRI resolution retrospectively. Our method learns a locally linear mapping between low-resolution and high-resolution volumetric image patches by employing random forest regression. We customize features suitable for volumetric MRI to train the random forest and propose a median tree ensemble for robust regression. VSRF outperforms state-of-the-art example-based super-resolution in terms of image quality and efficiency for model training and inference on different MRI datasets. It is also superior to unsupervised methods with just a handful or even a single volume to assemble training data.<br
Keywords: MRI; Super-resolution; Random forests

LONGITUDINAL CHANGE IN THE CENTRAL NERVOUS SYSTEM PAIN RESPONSE AFTER TREATMENT WITH CERTOLIZUMAB OR PLACEBO. A POST-HOC ANALYSIS FROM THE PRECEPRA TRIAL - Rech, Jürgen; Tascilar, K.; Schenker, Hannah; Hagen, Melanie; Sergeeva, Marina; Selvakumar, Mageshwar; Konerth, Laura; Prade, Jutta; Strobelt, Sandra; Schonau, V.; Valor, L.; Hueber, A.; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2020)
CRIS-Team WoS Importer:2020-08-21

Loss of fibulin-4 results in abnormal collagen fibril assembly in bone, caused by impaired lysyl oxidase processing and collagen cross-linking - Sasaki, Takako; Stoop, Reinout; Sakai, Takao; Heß, Andreas; Deutzmann, Rainer; Schlötzer-Schrehardt, Ursula; Chu, Mon-Li; Von Der Mark, Klaus (Matrix Biology, 2016)
The extracellular matrix protein fibulin-4 has been shown to be indispensable for elastic fiber assembly, but there is also evidence from human mutations that it is involved in controlling skeletal development and bone stability. Fibulin-4 mutations were identified in patients suffering from vascular abnormality and/or cutis laxa, and some of these patients exhibited bone fragility, arachnodactyly and joint laxity. In order to elucidate the role of fibulin-4 in bone structure and skeletal development, we analyzed structural changes in skeletal tissues of Fbln4(-/-) mice. Immunostaining confirmed that fibulin-4 is highly expressed in cartilage, bone, ligaments and tendons. No morphological abnormalities were found in the skeleton of Fbln4(-/-) mice as compared to wild type littermates except forelimb contractures as well as unusually thick collagen fibrils. Furthermore, fibulin-4 deficiency caused enhanced susceptibility of bone collagen for acid extraction, consistent with significantly reduced lysylpyridinoline and hydroxylysylpyridinoline cross-links in bone. In accordance with that, the amount of lysyl oxidase in long bones and calvaria was strongly decreased and proteolytic activation of lysyl oxidase was reduced in fibulin-4 deficient osteoblasts, while addition of recombinant fibulin-4 rescued the activation. The finding suggested that fibulin-4 is important for the proteolytic activation of lysyl oxidase which has a pivotal role in cross-linking of collagen and elastin.
EVALuna2:10209

Manganese-Enhanced Magnetic Resonance Imaging for Mapping of Whole Brain Activity Patterns Associated with the Intake of Snack Food in Ad Libitum Fed Rats - Hoch, Tobias; Kreitz, Silke; Gaffling, Simone; Pischetsrieder, Monika; Heß, Andreas (PLoS ONE, 2013)
Non-homeostatic hyperphagia, which is a major contributor to obesity-related hyperalimentation, is associated with the diet's molecular composition influencing, for example, the energy content. Thus, specific food items such as snack food may induce food intake independent from the state of satiety. To elucidate mechanisms how snack food may induce non-homeostatic food intake, it was tested if manganese-enhanced magnetic resonance imaging (MEMRI) was suitable for mapping the whole brain activity related to standard and snack food intake under normal behavioral situation. Application of the MnCl2 solution by osmotic pumps ensured that food intake was not significantly affected by the treatment. After z-score normalization and a non-affine three-dimensional registration to a rat brain atlas, significantly different grey values of 80 predefined brain structures were recorded in ad libitum fed rats after the intake of potato chips compared to standard chow at the group level. Ten of these areas had previously been connected to food intake, in particular to hyperphagia (e.g. dorsomedial hypothalamus or the anterior paraventricular thalamic nucleus) or to the satiety system (e.g. arcuate hypothalamic nucleus or solitary tract); 27 areas were related to reward/addiction including the core and shell of the nucleus accumbens, the ventral pallidum and the ventral striatum (caudate and putamen). Eleven areas associated to sleep displayed significantly reduced Mn2+-accumulation and six areas related to locomotor activity showed significantly increased Mn2+-accumulation after the intake of potato chips. The latter changes were associated with an observed significantly higher locomotor activity. Osmotic pump-assisted MEMRI proved to be a promising technique for functional mapping of whole brain activity patterns associated to nutritional intake under normal behavior.

Maternal immune activation during pregnancy impacts on brain structure and function in the adult offspring - Kreitz, Silke; Zambon, Alice; Ronovsky, Marianne; Budinsky, Lubos; Helbich, Thomas H.; Sideromenos, Spyros; Ivan, Claudiu-Ionut; Konerth, Laura; Wank, Isabel; Berger, Angelika; Pollak, Arnold; Heß, Andreas; et al. (Brain Behavior and Immunity, 2020)
Gestational infection constitutes a risk factor for the occurrence of psychiatric disorders in the offspring. Activation of the maternal immune system (MIA) with subsequent impact on the development of the fetal brain is considered to form the neurobiological basis for aberrant neural wiring and the psychiatric manifestations later in offspring life. The examination of validated animal models constitutes a premier resource for the investigation of the neural underpinnings.
CRIS-Team WoS Importer:2020-01-10

Molecular archaeology of human cognitive traits - Kaczanowska, Joanna; Ganglberger, Florian; Chernomor, Olga; Kargl, Dominic; Galik, Bence; Heß, Andreas; Moodley, Yoshan; von Haeseler, Arndt; Bühler, Katja; Haubensak, Wulf (Cell Reports, 2022)
The brains and minds of our human ancestors remain inaccessible for experimental exploration. Therefore, we reconstructed human cognitive evolution by projecting nonsynonymous/synonymous rate ratios (ω values) in mammalian phylogeny onto the anatomically modern human (AMH) brain. This atlas retraces human neurogenetic selection and allows imputation of ancestral evolution in task-related functional networks (FNs). Adaptive evolution (high ω values) is associated with excitatory neurons and synaptic function. It shifted from FNs for motor control in anthropoid ancestry (60–41 mya) to attention in ancient hominoids (26–19 mya) and hominids (19–7.4 mya). Selection in FNs for language emerged with an early hominin ancestor (7.4–1.7 mya) and was later accompanied by adaptive evolution in FNs for strategic thinking during recent (0.8 mya–present) speciation of AMHs. This pattern mirrors increasingly complex cognitive demands and suggests that co-selection for language alongside strategic thinking may have separated AMHs from their archaic Denisovan and Neanderthal relatives.
CRIS-Team Scopus Importer:2022-09-09
Keywords: archaic brains; attention; computational neuroanatomy; CP: Neuroscience; Denisovan; evolutionary genetics; human cognition; language; Neanderthal; neurogenetic evolution; strategic thinking

Neutral sphingomyelinase controls acute and chronic alcohol effects on brain activity - Wank, Isabel; Mittmann, Claire; Kreitz, Silke; Chestnykh, Daria; Mühle, Christiane; Kornhuber, Johannes; Ludwig, Andreas; Kalinichenko, Liubov; Müller, Christian P.; Heß, Andreas (Neuropharmacology, 2024)
Alcohol consumption is a widespread phenomenon throughout the world. However, how recreational alcohol use evolves into alcohol use disorder (AUD) remains poorly understood. The Smpd3 gene and its coded protein neutral sphingomyelinase (NSM) are associated with alcohol consumption in humans and alcohol-related behaviors in mice, suggesting a potential role in this transition. Using multiparametric magnetic resonance imaging, we characterized the role of NSM in acute and chronic effects of alcohol on brain anatomy and function in female mice. Chronic voluntary alcohol consumption (16 vol% for at least 6 days) affected brain anatomy in WT mice, reducing regional structure volume predominantly in cortical regions. Attenuated NSM activity prevented these anatomical changes. Functional MRI linked these anatomical adaptations to functional changes: Chronic alcohol consumption in mice significantly modulated resting state functional connectivity (RS FC) in response to an acute ethanol challenge (i.p. bolus of 2 g kg−1) in heterozygous NSM knockout (Fro), but not in WT mice. Acute ethanol administration in alcohol-naïve WT mice significantly decreased RS FC in cortical and brainstem regions, a key finding that was amplified in Fro mice. Regarding direct pharmacological effects, acute ethanol administration increased the regional cerebral blood volume (rCBV) in many brain areas. Here, chronic alcohol consumption otherwise attenuated the acute rCBV response in WT mice but enhanced it in Fro mice. Altogether, these findings suggest a differential role for NSM in acute and chronic functional brain responses to alcohol. Therefore, targeting NSM may be useful in the prevention or treatment of AUD.
CRIS-Team Scopus Importer:2024-05-03
Keywords: Alcohol use disorder; Anatomical MRI; fMRI; Neutral sphingomyelinase; rCBV; Resting state functional connectivity

Neutral sphingomyelinase mediates the co-morbidity trias of alcohol abuse, major depression and bone defects - Kalinichenko, Liubov; Mühle, Christiane; Jia, Tianye; Anderheiden, Felix; Datz, Maria; Eberle, Anna-Lisa; Eulenburg, Volker; Granzow, Jonas; Hofer, Martin Jürgen; Hohenschild, Julia; Huber, Sabine; Kämpf, Stefanie; et al. (Molecular Psychiatry, 2021)
Mental disorders are highly comorbid and occur together with physical diseases, which are often considered to arise from separate pathogenic pathways. We observed in alcohol-dependent patients increased serum activity of neutral sphingomyelinase. A genetic association analysis in 456,693 volunteers found associations of haplotypes of SMPD3 coding for NSM-2 (NSM) with alcohol consumption, but also with affective state, and bone mineralisation. Functional analysis in mice showed that NSM controls alcohol consumption, affective behaviour, and their interaction by regulating hippocampal volume, cortical connectivity, and monoaminergic responses. Furthermore, NSM controlled bone–brain communication by enhancing osteocalcin signalling, which can independently supress alcohol consumption and reduce depressive behaviour. Altogether, we identified a single gene source for multiple pathways originating in the brain and bone, which interlink disorders of a mental–physical co-morbidity trias of alcohol abuse—depression/anxiety—bone disorder. Targeting NSM and osteocalcin signalling may, thus, provide a new systems approach in the treatment of a mental–physical co-morbidity trias.
CRIS-Team Scopus Importer:2021-10-08

Non-homeostatic intake of snack foods: Molecular triggers and effects on brain activity pattern - Hoch, Tobias; Heß, Andreas; Pischetsrieder, Monika (The Chemical Sensory Informatics of Food: Measurement, Analysis, Integration, 2015)
Craving for special types of food like snack food can tremendously influence our energy balance. The result: obesity due to a non-homeostatic, hedonic food intake, i.e. an intake of energy independent of hunger and satiety. The intake of potato chips – an often craved highly palatable snack food – has a great influence on whole brain activity pattern. Especially the reward system as well as circuits regulating food intake, sleep and locomotor activity are affected. Furthermore, we could show that the fat and carbohydrate content is a main contributor to the palatability of potato chips. These first steps of the identification of the molecular triggers and the corresponding effects on brain activity pattern of the non-homeostatic intake of highly palatable snack food are reviewed in this chapter.
UnivIS-Import:2015-07-08:Pub.2015.nat.dchph.llmch.nonhom

On the Usage of Brain Atlases in Neuroimaging Research - Heß, Andreas; Hinz, Rukun; Keliris, Georgios A.; Boehm-Sturm, Philipp (Molecular Imaging and Biology, 2018)
Brain atlases play a key role in modern neuroimaging analysis of brain structure and function. We review available atlas databases for humans and animals and illustrate common state-of-the-art workflows in neuroimaging research based on image registration. Advances in noninvasive imaging methods, 3D ex vivo microscopy, and image processing are summarized which will eventually close the current resolution gap between brain atlases based on conventional 2D histology and those based on 3D in vivo imaging.
EVALuna2:213445

Pharmacological and resting state fMRI reveal Osteocalcin’s effects on mouse brain regions with high Gpr37 and Gpr158 expression - Freus, Natalia; Wank, Isabel; Häfele, Maximilian; Kalinichenko, Liubov; Müller, Christian P.; Strobelt, Sandra; Ludwig, Andreas; Heß, Andreas; Kreitz, Silke (Scientific Reports, 2025)
Osteocalcin (OCN) is an endocrine hormone that signals in the periphery, regulating male fertility, energy expenditure and glucose homeostasis. It can also cross the blood-brain-barrier and act on the brain via receptors GPR37 and GPR158. In the brain, OCN influences neurotransmitter synthesis of serotonin, norepinephrine, and dopamine. OCN’s function is related to cognitive and memory performance and lack of OCN is associated with anxiety and depression-like behavior in mice. We used multiparametric magnetic resonance imaging (MRI) including pharmacological MRI and resting state functional MRI, along with gene expression data for Gpr37 and Gpr158 to investigate the physiological effects of intravenously administered OCN on the wild type mouse brain. We found four core brain regions (brainstem, limbic output, association cortex, and basal ganglia) that are highly relevant in all three analytical modalities (i.e. pharmacological, resting state MRI and gene expression) and play therefore a major role in mediating OCN’s effect in the brain. This study provides the first imaging data of the physiological impact of OCN on the mouse brain, suggesting its potential role in modulating brain function and its relevance as a candidate for further investigation in anxiety, depression, and cognitive impairments.
CRIS-Team Scopus Importer:2025-04-01
Keywords: Allen brain atlas; Depression; Functional connectivity; Mouse fMRI; Osteocalcin; rCBV

PPARβ/δ governs Wnt signaling and bone turnover - Scholtysek, Carina; Katzenbeisser, Julia; Fu, He; Uderhardt, Stefan; Ipseiz, Natacha; Stoll, Cornelia; Zaiss, Mario; Stock, Michael; Donhauser, Laura-Robina; Boehm, Christina; Kleyer, Arnd; Heß, Andreas; et al. (Nature Medicine, 2013)
Peroxisome proliferator-activated receptors (PPARs) act as metabolic sensors and central regulators of fat and glucose homeostasis. Furthermore, PPAR? has been implicated as major catabolic regulator of bone mass in mice and humans. However, a potential involvement of other PPAR subtypes in the regulation of bone homeostasis has remained elusive. Here we report a previously unrecognized role of PPAR?/? as a key regulator of bone turnover and the crosstalk between osteoblasts and osteoclasts. In contrast to activation of PPAR?, activation of PPAR?/? amplified Wnt-dependent and ?-catenin-dependent signaling and gene expression in osteoblasts, resulting in increased expression of osteoprotegerin (OPG) and attenuation of osteoblast-mediated osteoclastogenesis. Accordingly, PPAR?/?-deficient mice had lower Wnt signaling activity, lower serum concentrations of OPG, higher numbers of osteoclasts and osteopenia. Pharmacological activation of PPAR?/? in a mouse model of postmenopausal osteoporosis led to normalization of the altered ratio of tumor necrosis factor superfamily, member 11 (RANKL, also called TNFSF11) to OPG, a rebalancing of bone turnover and the restoration of normal bone density. Our findings identify PPAR?/? as a promising target for an alternative approach in the treatment of osteoporosis and related diseases.
EVALuna2:8501

Predicting functional neuroanatomical maps from fusing brain networks with genetic information - Ganglberger, Florian; Kaczanowska, Joanna; Penninger, Josef M.; Heß, Andreas; Buehler, Katja; Haubensak, Wulf (NeuroImage, 2018)
Functional neuroanatomical maps provide a mesoscale reference framework for studies from molecular to systems neuroscience and psychiatry. The underlying structure-function relationships are typically derived from functional manipulations or imaging approaches. Although highly informative, these are experimentally costly. The increasing amount of publicly available brain and genetic data offers a rich source that could be mined to address this problem computationally. Here, we developed an algorithm that fuses gene expression and connectivity data with functional genetic meta data and exploits cumulative effects to derive neuroanatomical maps related to multi-genic functions. We validated the approach by using public available mouse and human data. The generated neuroanatomical maps recapture known functional anatomical annotations from literature and functional MRI data. When applied to multi-genic meta data from mouse quantitative trait loci (QTL) studies and human neuropsychiatric databases, this method predicted known functional maps underlying behavioral or psychiatric traits. Taken together, genetically weighted connectivity analysis (GWCA) allows for high throughput functional exploration of brain anatomy in silico. It maps functional genetic associations onto brain circuitry for refining functional neuroanatomy, or identifying trait-associated brain circuitry, from genetic data.
EVALuna2:213446

Prediction of Response to Certolizumab-Pegol in Rheumatoid Arthritis By Functional MRI of the Brain - an Interim Analysis of an Ongoing Investigator Initiated Phase III Trial - Schenker, Hannah; Heß, Andreas; Konerth, Laura; Sergeeva, Marina; Prade, Jutta; Kleyer, Arnd; Reiser, Michaela; Hueber, Axel; Englbrecht, Matthias; Feist, Eugen; Voll, Reinhard; Bannert, Bettina; et al. (2017)
EVALuna2:33139

Prediction of response to Certolizumab-Pegol in rheumatoid arthritis (PreCePRA) by functional MRI of the brain – Study protocol for a randomized double-blind controlled study - Schenker, Hannah; Tascilar, Koray; Konerth, Laura; Sergeeva, Marina; Prade, Jutta; Strobelt, Sandra; Kleyer, Arnd; Simon, David; Mendez, L.; Hagen, Melanie; Schönau, V.; Hueber, A.; et al. (Contemporary Clinical Trials Communications, 2021)
Background: Tumor necrosis factor inhibitors (TNFi) signify a major advance in the treatment of rheumatoid arthritis (RA). However, treatment success initially remains uncertain as approximately half of the patients do not respond adequately to TNFi. Thus, an unmet need exists to better predict therapeutic outcome of biologicals. Objectives: We investigated whether brain activity associated with arthritis measured by functional magnetic resonance imaging (fMRI) of the brain can serve as a predictor of response to TNFi in RA patients. Methods: PreCePRA is a multi-center, randomized, double-blind, placebo-controlled fMRI trial on patients with RA [1] [2]. Active RA patients failing csDMARDs therapy with a DAS28 > 3.2 and at least three tender and/or swollen joints underwent a brain BOLD (blood-oxygen-level dependent) fMRI scan upon joint compression at screening. Patients were then randomized into a 12-week double-blinded treatment phase with 200 mg Certolizumab Pegol (CZP) every two weeks (arm 1: fMRI BOLD signal activated volume > 2000 voxel, i.e. 2 cm3; arm 2: fMRI BOLD signal activated volume <2000 voxel) or placebo (arm 3). DAS28 low disease activity at 12 weeks was assigned as primary endpoint. A 12-week follow-up phase in which patients were switched from the placebo to the treatment arm followed the blinded phase. fMRI was carried out at screening as well as after 12 and 24 weeks of receiving CZP or placebo. Conclusion: We hypothesize that high-level central nervous representation of pain in patients with rheumatoid arthritis predicts response to the TNFi CZP which we further investigate in the PreCePRA trial.
CRIS-Team Scopus Importer:2021-06-04
Keywords: functional MRI; Neuroimaging; Rheumatoid arthritis; TNF inhibition

PREDICTION OF RESPONSE TO CERTOLIZUMAB PEGOL TREATMENT BY FUNCTIONAL MRI OF THE BRAIN: AN INTERNATIONAL, MULTI-CENTER, RANDOMIZED, DOUBLE-BLIND, PLACEBO-CONTROLLED TRIAL (PRECEPRA) - Rech, Jürgen; Tascilar, K.; Schenker, Hannah; Sergeeva, Marina; Selvakumar, Mageshwar; Konerth, Laura; Prade, Jutta; Strobelt, Sandra; Hagen, Melanie; Schonau, V.; Valor, L.; Hueber, A.; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2020)
CRIS-Team WoS Importer:2020-08-21

Quantification of plaque lipids in the aortic root of ApoE-deficient mice by 3D DIXON magnetic resonance imaging in an ex vivo model - Dietel, Barbara; Budinsky, Lubos; Kühn, Constanze; Uder, Michael; Achenbach, Stephan; Heß, Andreas (European Radiology, 2015)
To establish a dedicated protocol for the three-dimensional (3D) quantification of plaque lipids in apolipoprotein E-deficient (apoE(-/-)) mice using ex vivo MRI.ApoE(-/-) mice were fed a high-fat diet (n = 10) or normal food (n = 10) for 3 months. Subsequently, a 3D FLASH MRI sequence was used to view the anatomy of the aortic root in the isolated hearts, where a 3D double-echo two-excitation pulse sequence (DIXON sequence) was used to selectively image plaque lipids. The vessel wall, lumen and plaque lipid volumes were quantified by MRI and histology for correlation analysis.DIXON MRI allowed visualisation and accurate quantification of plaque lipids. When comparing the vessel wall, lumen and plaque lipid sizes in the aortic root, Bland-Altman and linear regression analysis revealed a close correlation between MRI results and the histological data both on a slice-by-slice basis and of the volumetric measurements (vessel wall: r (2) = 0.775, p < 0.001; vessel lumen: r (2) = 0.875; p = 0.002; plaque lipid: r (2) = 0.819, p = 0.003).The combination of 3D FLASH and DIXON-sequence MRI permits an accurate ex vivo assessment of the investigated plaque parameters in the aortic root of mice, particularly the lipid content.o Ex vivo MRI allows high resolution quantification of plaque parameters in mice o DIXON MRI enables visualisation of plaque lipids in the aortic root of mice o A close correlation between histology and MRI quantifies plaque parameters o Preservation of tissue integrity allows additional analysis to be performed o Short measurement time may permit the translation into in vivo measurements.
EVALuna2:11953

Regulatory T cells protect from local and systemic bone destruction in arthritis. - Zaiss, Mario; Frey, Benjamin; Heß, Andreas; Zwerina, Jochen; Luther, Julia; Nimmerjahn, Falk; Engelke, Klaus; Kollias, George; Huenig, Thomas; Schett, Georg; David, Jean-Pierre (Journal of Immunology, 2010)
We previously demonstrated the suppressive effects of regulatory T cells (Treg cells) on osteoclast differentiation in vitro. In this article, we show that blood markers of bone resorption inversely correlate with the amount of circulating Treg cells in healthy controls and rheumatoid arthritis patients, further suggesting that Treg cells may control bone destruction in vivo. Indeed, bone marrow from Foxp3-transgenic (Foxp3tg) mice fully protected human TNF transgenic (hTNFtg) mice from TNF-alpha-induced bone destruction, whereas Foxp3-deficient bone marrow enhanced local and systemic bone loss. The same protective effect was also obtained by treating hTNFtg mice with the CD28 superagonist mAb (CD28 SA), which increased Treg cell numbers. In both models, bone protection by Treg cells was associated with reduced osteoclast numbers, resulting in less bone-resorbing activity. Reduced osteoclast numbers were not caused by an intrinsic defect in osteoclast differentiation because osteoclast precursors from hTNFtg/Foxp3tg chimeras responded normally to M-CSF and receptor activator of NF-kappaB ligand. Although a decrease in the clinical signs of arthritis was observed in Foxp3tg bone marrow-transferred and CD28 SA-treated hTNFtg mice, the bone-protective effect of Treg cells was independent of the suppression of inflammation, as demonstrated by the increased systemic bone density observed in wild-type mice treated with CD28 SA. This work demonstrated that increasing Treg cell numbers improved clinical signs of arthritis and suppressed local and systemic bone destruction. Thus, enhancing the activity of Treg cells would be beneficial for the treatment of inflammation-induced bone loss observed in rheumatoid arthritis.

Reply to Hou: Central nervous system effects of TNF-α blockade - Heß, Andreas; Rech, Jürgen; Brune, Kay; Schett, Georg (Proceedings of the National Academy of Sciences of the United States of America, 2011)
CRIS-Team Scopus Importer:2021-02-03

Research consortium Neuroimmunology and pain in the research network musculoskeletal diseases - Schaible, H-G.; Chang, H. -D.; Graessel, S.; Haibel, H.; Heß, Andreas; Kamradt, T.; Radbruch, A.; Schett, Georg; Stein, C.; Straub, R. H. (Zeitschrift für Rheumatologie, 2018)
BACKGROUND: The research consortium Neuroimmunology and Pain (Neuroimpa) explores the importance of the relationships between the immune system and the nervous system in musculoskeletal diseases for the generation of pain and for the course of fracture healing and arthritis. MATERIAL AND METHODS: The spectrum of methods includes analyses at the single cell level, in vivo models of arthritis and fracture healing, imaging studies on brain function in animals and humans and analysis of data from patients. RESULTS: Proinflammatory cytokines significantly contribute to the generation of joint pain through neuronal cytokine receptors. Immune cells release opioid peptides which activate opioid receptors at peripheral nociceptors and thereby evoke hypoalgesia. The formation of new bone after fractures is significantly supported by the nervous system. The sympathetic nervous system promotes the development of immune-mediated arthritis. The studies show a significant analgesic potential of the neutralization of proinflammatory cytokines and of opioids which selectively inhibit peripheral neurons. Furthermore, they show that the modulation of neuronal mechanisms can beneficially influence the course of musculoskeletal diseases. DISCUSSION: Interventions in the interactions between the immune system and the nervous system hold a great therapeutic potential for the treatment of musculoskeletal diseases and pain.
EVALuna2:34149

Response to peripheral immune stimulation within the brain: magnetic resonance imaging perspective of treatment success - Sergeeva, Marina; Rech, Juergen; Schett, Georg; Heß, Andreas (Arthritis Research & Therapy, 2015)
Chronic peripheral inflammation in diseases such as rheumatoid arthritis leads to alterations in central pain processing and consequently to mood disorders resulting from sensitization within the central nervous system and enhanced vulnerability of the medial pain pathway. Proinflammatory cytokines such as tumor necrosis factor (TNF) alpha play an important role herein, and therapies targeting their signaling (i.e., anti-TNF therapies) have been proven to achieve good results. However, the phenomenon of rapid improvement in the patients' subjective feeling after the start of TNF? neutralization remained confusing, because it was observed long before any detectable signs of inflammation decline. Functional magnetic resonance imaging (fMRI), enabling visualization of brain activity upon peripheral immune stimulation with anti-TNF, has helped to clarify this discrepancy. Moreover, fMRI appeared to work as a reliable tool for predicting prospective success of anti-TNF therapy, which is valuable considering the side effects of the drugs and the high therapy costs. This review, which is mainly guided by neuroimaging studies of the brain, summarizes the state-of-the-art knowledge about communication between the immune system and the brain and its impact on subjective well-being, addresses in more detail the outcome of the abovementioned anti-TNF fMRI studies (rapid response to TNF? blockade within the brain pain matrix and differences in brain activation patterns between prospective therapy responders and nonresponders), and discusses possible mechanisms for the latter phenomena and the predictive power of fMRI.
EVALuna2:13172

Sensory cortex lesion triggers compensatory neuronal plasticity - Depner, Manfred; Tziridis, Konstantin; Heß, Andreas; Schulze, Holger (BMC Neuroscience, 2014)
Lesions to the human brain often cause dramatic impairments in the life of patients because of the very limited capacity of the mammalian nervous system to regenerate. On the other hand, neuronal tissue has a high capacity to reorganize itself so that loss of function due to brain damage may be compensated through neuroplastic reorganization of undamaged tissue in brain regions adjacent or contralateral to the lesion site. In this study we investigated the effect of serial lesions of the auditory cortices (AC) in both hemispheres of Mongolian gerbils on discrimination performance for fast amplitude modulated tones (AM). Healthy animals were trained to discriminate two fast AM, an ability that has previously been shown to critically depend on cortical processing. Their ability to maintain significant discrimination performance was retested after unilateral AC lesion, and again after lesion of the contralateral AC, with 15 days of continuing training in between the two lesions.After bilateral cortical ablation of both AC and 45 days of training the animals show no change in pure tone detection threshold as measured with modulation of the acoustic startle reflex which has been shown to rely on subcortical structures. In contrast to simultaneous bilateral ablation of AC that results in complete loss of AM discrimination ability in this paradigm we found compensatory plasticity that seems to be triggered by unilateral cortical ablation with subsequent training and that is able to almost fully compensate for the lost cortical functions.Our results demonstrate that AM discrimination ability that normally depends on AC may be transferred to other brain regions when the brain has time to activate compensatory plasticity between the lesions of the two AC hemispheres. For this process to take place obviously one intact AC hemisphere is needed. This finding may open perspectives for new therapeutic strategies that may alleviate the impairments after multiple ischemic strokes.
EVALuna2:8518

Snack food intake in ad libitum fed rats is triggered by the combination of fat and carbohydrates - Hoch, Tobias; Pischetsrieder, Monika; Heß, Andreas (Frontiers in Psychology, 2014)
Snack food like potato chips substantially contributes to energy intake in humans. In contrast to basic food, snacks are consumed additionally to other meals and may thereby lead to non-homeostatic energy intake. Snack food is also frequently associated with hedonic hyperphagia, a food intake independent from hunger. Analysis of brain activity patterns by manganese-enhanced MRI has previously revealed that the intake of potato chips in ad libitum fed rats strongly activates the reward system of the rat brain, which may lead to hedonic hyperphagia. The purpose of the present study was to develop a two-choice preference test to identify molecular determinants of snack food triggering extra food intake in ad libitum fed rats. Different kinds of test food were presented three times a day for 10 min each time. To minimize the influence of organoleptic properties, each test food was applied in a homogenous mixture with standard chow. Food intake as well as food intake-related locomotor activity were analyzed to evaluate the effects induced by the test foods in the two-choice preference test. In summary, fat (F), carbohydrates (CH), and a mixture of fat and carbohydrates (FCH) led to a higher food intake compared to standard chow. Notably, potato chip test food (PC) was highly significantly preferred over standard chow (STD) and also over their single main macronutrients F and CH. Only FCH induced an intake comparable to PC. Despite its low energy density, fat-free potato chip test food (ffPC) was also significantly preferred over STD and CH, but not over F, FCH, and PC. Thus, it can be concluded that the combination of fat and carbohydrates is a major molecular determinant of potato chips triggering hedonic hyperphagia. The applied two-choice preference test will facilitate future studies on stimulating and suppressive effects of other food components on non-homeostatic food intake. © 2014 Hoch, Pischetsrieder and Hess.
UnivIS-Import:2015-03-09:Pub.2014.nat.dchph.llmch.snackf
Keywords: Eating behavior; Food intake; Macronutrients; Preference test; Rat; Snack food

The complement system drives local inflammatory tissue priming by metabolic reprogramming of synovial fibroblasts - Friščić, Jasna; Böttcher, Martin; Reinwald, Christiane; Bruns, Heiko; Wirth, Benjamin; Popp, Sebastian; Walker, Kellie Irene; Ackermann, Jochen A.; Chen, Xi; Turner, Jason; Zhu, Honglin; Seyler, Lisa; et al. (Immunity, 2021)
Arthritis typically involves recurrence and progressive worsening at specific predilection sites, but the checkpoints between remission and persistence remain unknown. Here, we defined the molecular and cellular mechanisms of this inflammation-mediated tissue priming. Re-exposure to inflammatory stimuli caused aggravated arthritis in rodent models. Tissue priming developed locally and independently of adaptive immunity. Repeatedly stimulated primed synovial fibroblasts (SFs) exhibited enhanced metabolic activity inducing functional changes with intensified migration, invasiveness and osteoclastogenesis. Meanwhile, human SF from patients with established arthritis displayed a similar primed phenotype. Transcriptomic and epigenomic analyses as well as genetic and pharmacological targeting demonstrated that inflammatory tissue priming relies on intracellular complement C3- and C3a receptor-activation and downstream mammalian target of rapamycin- and hypoxia-inducible factor 1α-mediated metabolic SF invigoration that prevents activation-induced senescence, enhances NLRP3 inflammasome activity, and in consequence sensitizes tissue for inflammation. Our study suggests possibilities for therapeutic intervention abrogating tissue priming without immunosuppression.
CRIS-Team Scopus Importer:2021-04-19
Keywords: arthritis; cell metabolism; cellular senescence; complement system; inflammasome; inflammation; mechanistic target of rapamycin; synovial fibroblasts; tissue priming; trained immunity

The impact of HCN4 channels on CNS brain networks as a new target in pain development - Häfele, Maximilian; Kreitz, Silke; Ludwig, Andreas; Heß, Andreas; Wank, Isabel (Frontiers in Network Physiology, 2023)
While it is well established that the isoform 2 of the hyperpolarization-activated cyclic nucleotide-gated cation channel (HCN2) plays an important role in the development and maintenance of pain, the role of the closely related HCN4 isoform in the processing of nociceptive signals is not known. HCN4 channels are highly expressed in the thalamus, a region important for stimulus transmission and information processing. We used a brain-specific HCN4-knockout mouse line (HCN4-KO) to explore the role of HCN4 channels in acute nociceptive processing using several behavioral tests as well as a multimodal magnetic resonance imaging (MRI) approach. Functional MRI (fMRI) brain responses were measured during acute peripheral thermal stimulation complemented by resting state (RS) before and after stimulation. The data were analyzed by conventional and graph-theoretical approaches. Finally, high-resolution anatomical brain data were acquired. HCN4-KO animals showed a central thermal, but not a mechanical hypersensitivity in behavioral experiments. The open field analysis showed no significant differences in motor readouts between HCN4-KO and controls but uncovered increased anxiety in the HCN4-KO mice. Thermal stimulus-driven fMRI (s-fMRI) data revealed increased response volumes and response amplitudes for HCN4-KO, most pronounced at lower stimulation temperatures in the subcortical input, the amygdala as well as in limbic/hippocampal regions, and in the cerebellum. These findings could be cross-validated by graph-theoretical analyses. Assessment of short-term RS before and after thermal stimulation revealed that stimulation-related modulations of the functional connectivity only occurred in control animals. This was consistent with the finding that the hippocampus was found to be smaller in HCN4-KO. In summary, the deletion of HCN4 channels impacts on processing of acute nociception, which is remarkably manifested as a thermal hypersensitive phenotype. This was mediated by the key regions hypothalamus, somatosensory cortex, cerebellum and the amygdala. As consequence, HCN4-KO mice were more anxious, and their brain-wide RS functional connectivity could not be modulated by thermal nociceptive stimulation.
Created from Fastlane, Scopus look-up
Keywords: BOLD-fMRI; graphtheory; HCN4 channels; knockout mice; multi modal MRI; pain; resting state-fMRI; thermal hypersensitivity